Ladder Drill Training on the Agility of Beginner Badminton Athletes - Jodi Gandala Putra; Silvi Aryanti; Ahmad Richard Victorian (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2023)
This study aims to determine the effect of ladder drill training on novice male badminton athletes at U 12-13 Club PB Pusri Palembang. The method used in this research is experimental, which means a sample is given a treatment. The research design used is One Group Pretest-Posttest Design. This sampling technique used total population sampling with a sample size of 30 athletes. The instrument of this research is agility. From the results of data processing and analysis using the data normality test, homogeneity test and hypothesis test using the T test formula, the results were that ladder drill training alone increased agility abilities in novice male badminton athletes. This can be seen from the results of data analysis through calculating the t test formula with the calculated t criterion being greater than ttable (14.730 ˃ 1.70) with a confidence level of 0.95 (α = 0.05) and the number of samples (N = 30). The implications of ladder drill training can have an influence on increasing agility in novice male badminton athletes U 12-13 Club PB Pusri Palembang.